Influence of native plant species on substrate moisture content behaviour within extensive green roof system - Chow M.F.; Bakar M.F.A.; Arenanda V. (American Institute of Physics Inc., 2023)
Green (vegetated) roofs are gaining the popularity in recent years as the green technology to meet the environmental sustainability and low-carbon targets in urban cities. Green roofs are useful in mitigating the stormwater runoff and urban heat island in the urban environment. The plant species played an important role on the hydrological performance of green roof. The study of moisture content behavior in extensive green roof system is still lacking in Malaysia. Therefore, this study is embarked to investigate the soil moisture content behavior in extensive green roof during dry periods within extensive green roof system with respect to different native plant species in Malaysia. A total of six green roof testbeds which vary systematically in their vegetation options (namely, Nephrolepis biserrata (fern), Cow Grass, Philippine Carpet Grass, Portulaca Grandiflora Cultivars (sedum)) were setup in the civil engineering laboratory. The substrate volumetric moisture content (VMC) was recorded by using TDR 100 soil moisture meter at every three hours interval. The highest VMC value was recorded by carpet grass followed by fern, cow grass, sedum, bare soil and finally the mixed plants. This study suggested that sedum species or mixed plant species are the most suitable to be planted in extensive green roof in tropical climate country. 2019 Author(s).